2011
DOI: 10.1007/s00464-011-1833-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision versus conventional laparoscopic sigmoid colectomy: a case-matched series

Abstract: Compared with conventional laparoscopic technique, single-incision laparoscopic surgery results in similar intraoperative and postoperative outcomes. The technique avoids use of multiple trocar sites and may safely be performed in patients with a history of previous abdominal surgery while maintaining a short length of hospital stay and low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 41 publications
1
35
2
2
Order By: Relevance
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 47%
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 47%
“…Some reports have successfully mentioned its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain, and shorter recovery time. [13][14][15][16][17] To our knowledge, this is the first reported case of SILSþ1 TPE for advanced rectal cancer.…”
Section: Discussionmentioning
confidence: 72%
“…Some reports have successfully mentioned advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain, and shorter recovery time; however, there are some technical complexities, such as instrument crowding, insufficient counter traction. [11][12][13][14][15][16] For rectal cancer, cases where laparoscopic surgery was performed using SILS þ 1 10 and where TME þ LPLD was performed with multiport laparoscopic surgery 17 have been reported, both of which take advantage of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%